Tumour stroma‐derived lipocalin‐2 promotes breast cancer metastasis. Issue 3 (29th April 2016) - Ören, Bilge; Urosevic, Jelena; Mertens, Christina; Mora, Javier; Guiu, Marc; Gomis, Roger R; Weigert, Andreas; Schmid, Tobias; Grein, Stephan; Brüne, Bernhard; Jung, Michaela
Abstract: Tumour cell‐secreted factors skew infiltrating immune cells towards a tumour‐supporting phenotype, expressing pro‐tumourigenic mediators. However, the influence of lipocalin‐2 (Lcn2) on the metastatic cascade in the tumour micro‐environment is still not clearly defined. Here, we explored the role of stroma‐derived, especially macrophage‐released, Lcn2 in breast cancer progression. Knockdown studies and neutralizing antibody approaches showed that Lcn2 contributes to the early events of metastasis in vitro . The release of Lcn2 from macrophages induced an epithelial–mesenchymal transition programme in MCF‐7 breast cancer cells and enhanced local migration as well as invasion into the extracellular matrix, using a three‐dimensioanl (3D) spheroid model. Moreover, a global Lcn2 deficiency attenuated breast cancer metastasis in both the MMTV–PyMT breast cancer model and a xenograft model inoculating MCF‐7 cells pretreated with supernatants from wild‐type and Lcn2‐knockdown macrophages. To dissect the role of stroma‐derived Lcn2, we employed an orthotopic mammary tumour mouse model. Implantation of wild‐type PyMT tumour cells into Lcn2‐deficient mice left primary mammary tumour formation unaltered, but specifically reduced tumour cell dissemination into the lung. We conclude that stroma‐secreted Lcn2 promotes metastasis in vitro and in vivo, thereby contributing to tumour progression. Our study highlights the tumourigenic potential of stroma‐released Lcn2 and suggests Lcn2 as a putative therapeutic target. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.